2014
DOI: 10.12944/cwe.9.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Tannery Wastewater by Chromium Resistant Fungal Isolate Fusarium chlamydosporium SPFS2-g

Abstract: The present study assessed the bioremediation potential of Fusarium chlamydosporium SPFS2-g isolated from tannery effluent enriched soil. The isolate exhibited minimum inhibitory concentration (MIC) for Cr(VI) as 500 ppm. The treatment of tannery wastewater with Fusarium chlamydosporium in shake flask experiment resulted in the reduction of chemical oxygen demand (COD), color, Cr(VI), total suspended solids (TSS), turbidity, Na + , Cl -, and NO 3 -in the order of 71. 80, 64.69, 100, 36.47, 22.77, 11.69, 27.87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 28 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…As per the Langmuir sorption isotherm [5], the most of the adsorption happens when a saturated monolayer of solute molecules is present on the adsorbent surface, there is no migration of adsorbate molecules in the surface plane when the energy of adsorption is constant. The Freundlich adsorption isotherm [6] is the initial isotherm which discusses the mathematical relationship for reversible and non-ideal adsorption. The theory of this model is not limited to the formation of a monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…As per the Langmuir sorption isotherm [5], the most of the adsorption happens when a saturated monolayer of solute molecules is present on the adsorbent surface, there is no migration of adsorbate molecules in the surface plane when the energy of adsorption is constant. The Freundlich adsorption isotherm [6] is the initial isotherm which discusses the mathematical relationship for reversible and non-ideal adsorption. The theory of this model is not limited to the formation of a monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…Many fungi have the ability to biosorb and bioaccumulate metals and are involved in the reduction of hexavalent chromium to trivalent chromium (Arévalo-Rangel et al, 2013). Fungal/microbial treatment methods for decolourisation and detoxification of industrial effluents have been reported earlier (Sharma and Malaviya, 2014;Choi et al, 2014;Hossain and Ismail, 2015;Hossain et al, 2016). Lignolytic fungi produce a special group of enzymes such as lignin peroxidase, manganese peroxidase and laccases, which are involved in the degradation and break down of complex aromatic polymers such as lignin and structurally complex toxic environmental pollutants (Bonugli-Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is often reported how metals can cause a general inhibition of microbial metabolism and of some basic traceable activities like nitrogen transformations, respiration, and organic matter decomposition (Baldrian et al 2000;Wuana et al 2014). However, fewer studies have focused on fungal behaviour when metals and xenobiotics are both present at potentially toxic concentrations, and what impact different toxic metals may have on organic pollutant biodegradation (Gharieb 2002;Sharaf and Alharbi 2013;Ma et al 2014;Sharma and Malaviya 2014;Urík et al 2014;Fuentes et al 2016;Jia et al 2017;Ma et al 2017;Ceci et al 2018). This review will discuss the situation in which filamentous fungi degrade xenobiotic substances in the presence of toxic metals or in extreme chemical conditions.…”
Section: Introductionmentioning
confidence: 99%